PENGARUH PENERAPAN MODEL PEMBELAJARAN KOOPERATIF TIPE WRITE-PAIR-SHARE (WPS) TERHADAP PEMAHAMAN KONSEP MATEMATIS SISWA KELAS VIII SMPN 6 LINGGO SARI BAGANTI - Fattriani, Yuri; K, Delsi; Febriana, Rina (STKIP PGRI Sumbar, 2013)
This research had background the lack of problem about students are less serious in that exercisegiven teacher and studentsâ comprehensionâs mathematical concept. This research had a purpose to know that studentsâ comprehension mathematical concept in which the learning model applied was Cooperative Write-Pair-Share Â type, better than studentsâ comprehension in was conventional learning at grade VIII of SMPN 6 Linggo Sari Baganti. Type of this research was experimental by research with random research design on the subject. Data analysis was done by using t-test with MINITABâs software. Result of hypothesis testing, the researcher got p-value= 0,015 < , thus the hypothesis of this research was accepted. There can be concluded that studentsâ comprehension mathematical concept in which the teaching model applied was cooperaive learning write-Pair-Share type, was better than studentsâ comprehension of mathematical concept in which the applied was by conventional learning at grade VIII of SMPN 6 Linggo Sari Baganti.